2016
DOI: 10.21272/jnep.8(4(2)).04074
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Nanocomposite Nanoporous Carbon / Nickel Hydroxide

Abstract: The electrochemical properties of composite nanoporous carbon / nickel hydroxide as electrode material for hybrid supercapacitors were investigated. Fast reversible faradaic reactions flow was determined in connection with chemical makeup of the -Ni(OH)2/С composite. It is shown that increase of nickel hydroxide concentration can intensify reactions. It is found that clean -Ni(OH)2 has 238 F/g of specific capacity, but -Ni(OH)2/С nanocomposite with 90 % nickel hydroxide has 292 F/g. Such capacity value can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…3). In electrochemical studies of α and β phases of nickel hydroxide [17,18] was found that the oxidation peaks lie in the range of 0.29-0.5 V for both phases, while the cathodic reduction peaks at 0.24 V for β-Ni(OH)2 and 0.16 V for α-Ni(OH)2, which agrees with the results obtained for initial NiMoO4 in this work.…”
Section: Resultssupporting
confidence: 90%
“…3). In electrochemical studies of α and β phases of nickel hydroxide [17,18] was found that the oxidation peaks lie in the range of 0.29-0.5 V for both phases, while the cathodic reduction peaks at 0.24 V for β-Ni(OH)2 and 0.16 V for α-Ni(OH)2, which agrees with the results obtained for initial NiMoO4 in this work.…”
Section: Resultssupporting
confidence: 90%
“…Another promising solution is an asymmetric hybrid supercapacitor (HS) that combines a non-Faradaic double-layer capacitive electrode based on activated carbon with a transition metal oxide electrode. Layered transition metal hydroxides and sulfides are the promising electrode materials for HS [1][2][3][4]. Among them ultrafine nickel hydroxide is attractive for investigations due to its * E-mail: kotsuybynsky@gmail.com structural and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…In NiMoO4 / C composites, the content of carbon material was 1, 5 and 10 % by weight, as it was found [9] that in the mechano-chemical synthesis of materials, the highest specific capacitance is achieved by a composite based on nickel hydroxide with a carbon content of 10 %. Therefore, we formed four NiMoO4 / C composites with carbon content: 1 and 10% (without ultrasonic exposure) and 1 and 5 % (carbon material was subjected to ultrasonic dispersion (denoted as С us)).…”
Section: Resultsmentioning
confidence: 98%